Freaky Friday (2003) [videorecording (DVD)] - Curtis, Jamie Lee, 1958-; Lohan, Lindsay, 1986-; Harmon, Mark, 1951-; Gould, Harold, 1923-2010; Murray, Chad Michael, 1981-; Rodgers, Mary, 1931-2014 (Disney DVD., 2003)
A mother and her daughter are always fighting and screaming at each other. Each thinks that the other has it so easy. Then, thanks to a magical fortune cookie, they switch personalities and bodies and discover each other's problems and complications. And they end up gaining a little respect for each other's point of view. But they need to be changed back by Saturday, because the mother is getting married!